Chemical, Metabolic, and Cellular Characterization of a FtsZ Inhibitor Effective Against Burkholderia cenocepacia - Chiarelli, Laurent R.; Scoffone, Viola Camilla; Trespidi, Gabriele; Barbieri, Giulia; Riabova, Olga; Monakhova, Natalia; Porta, Alessio; Manina, Giulia; Riccardi, Giovanna; Makarov, Vadim; Buroni, Silvia (Frontiers in Microbiology, 2020)
There is an urgent need for new antimicrobials to treat the opportunistic Gram-negative Burkholderia cenocepacia, which represents a problematic challenge for cystic fibrosis patients. Recently, a benzothiadiazole derivative, C109, was shown to be effective against the infections caused by B. cenocepacia and other Gram-negative and –positive bacteria. C109 has a promising cellular target, the cell division protein FtsZ, and a recently developed PEGylated formulation make it an attractive molecule to counteract Burkholderia infections. However, the ability of efflux pumps to extrude it out of the cell represents a limitation for its use. Here, more than 50 derivatives of C109 were synthesized and tested against Gram-negative species and the Gram-positive Staphylococcus aureus. In addition, their activity was evaluated on the purified FtsZ protein. The chemical, metabolic and cellular stability of C109 has been assayed using different biological systems, including quantitative single-cell imaging. However, no further improvement on C109 was achieved, and the role of efflux in resistance was further confirmed. Also, a novel nitroreductase that can inactivate the compound was characterized, but it does not appear to play a role in natural resistance. All these data allowed a deep characterization of the compound, which will contribute to a further improvement of its properties.